Effects of Vitamin D Receptor Knockout on Cornea Epithelium Gap Junctions - Lu, Xiaowen (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. Gap junctions are present in all corneal cell types and have been shown to have a critical role in cell phenotype determination. Vitamin D has been shown to influence cell differentiation, and recent work demonstrates the presence of vitamin D in the ocular anterior segment. This study measured and compared gap junction diffusion coefficients among different cornea epithelium phenotypes and in keratocytes using a noninvasive technique, fluorescence recovery after photobleaching (FRAP), and examined the influence of vitamin D receptor (VDR) knockout on epithelial gap junction communication in intact corneas. Previous gap junction studies in cornea epithelium and keratocytes were performed using cultured cells or ex vivo invasive techniques. These invasive techniques were unable to measure diffusion coefficients and likely were disruptive to normal cell physiology. METHODS. Corneas from VDR knockout and control mice were stained with 5(6)-carboxyfluorescein diacetate (CFDA). Gap junction diffusion coefficients of the corneal epithelium phenotypes and of keratocytes, residing in intact corneas, were detected using FRAP. RESULTS. Diffusion coefficients equaled 18.7, 9.8, 5.6, and 4.2 μm(2)/s for superficial squamous cells, middle wing cells, basal cells, and keratocytes, respectively. Corneal thickness, superficial cell size, and the superficial squamous cell diffusion coefficient of 10-week-old VDR knockout mice were significantly lower than those of control mice (P < 0.01). The superficial cell diffusion coefficient of heterozygous mice was significantly lower than control mice (P < 0.05). CONCLUSIONS. Our results demonstrate differences in gap junction dye spread among the epithelial cell phenotypes, mirroring the epithelial developmental axis. The VDR knockout influences previously unreported cell-to-cell communication in superficial epithelium.